EFEKTIVITAS INSTITUSI HUKUM DALAM PENEGAKKAN HUKUM TINDAK PIDANA KORUPSI DAN IMPLIKASINYA TERHADAP KETAHANAN HUKUM (Studi : Di Kabupaten Muna Propinsi Sulawesi Tenggara) - , LA ODE MOHAMMAD SAYIDIMAN, SH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Corruption has plagued this country since long time ago in a large-scale and almost touches all aspects of life from the center to the regions, without exception for Muna Regency in Southeast Sulawesi Province. Corruption has entered a very complex phase, this is supposed because of the effectiveness of legal institutions in law enforcement of crime corruption have not been as effective as expected, this study aims to determine the effectiveness of legal institutions (Indonesian Police, The Prosecutor, and The Court) in the law crime corruption enforcement in Muna Regency, and their implications to the resilience of law in Muna Regency. The study was conducted in Muna Regency Southeast Sulawesi Province by using survey methods. Number of samples are 30 respondents. The variable in this research is the effectiveness of legal institutions (Muna Police, Raha District Prosecutor, and Raha Court) in law crime corruption enforcement in Muna Regency and the resilience of law conditions in Muna Regency. The results of this study indicate that the effectiveness of legal institutions in law crime corruption enforcement in Muna Regency is not in a good condition. It implicates to the legal enforcement conditions in Muna Regency at this time, which the first of the five categories is: "Very Tough", the second : "Tough.", the third "Fair Tough", the fourth "Less Tough" and the fifth "Prone/Danger". Based on the analysis results and the discussion, the conditions research in Muna Regency in the current resilience of law is categorized as "Fair tough" and it is still far from the category of "Very Tough". The Implications/influences the effectiveness of legal institutions in law enforcement corruption cases against the law in Muna Regency Southeast Sulawesi Province were measured using the SPSS statistical gauge and the effect is significant because = 3.792, p = 0.001 < 0.005. The influence = 33.9% and the rest = 66.1% influenced by other factors which were not examined by the author.